Oxytocin Hormone Induction on Milk Production in Relation to Dairy Kid Performance - Sumaryadi, Mas Yedi; Saleh, Dadang Mulyadi; Nugroho, Aras Prasetiyo; Hidayat, Nu'man; Hidayah, Chomsiatun Nurul (ANIMAL PRODUCTION, 2019)
The application of oxytocin induction to milk production in relation to the performance of kids in dairy goats had been carried out in the "PEGUMAS" dairy goat farmer group Gumelar District, Banyumas. This activity aimed to increase milk production and kid performance through the induction of the hormone oxytocin in dairy goats. The approach method was designed in two stages: the first stage carried out the socialization activities and demonstration of techniques for applying IPTEKS, and the second stage applied hormonal technology in the form of oxytocin hormone induction in dairy goats. The material used was dairy goat parity I aged 1.5 - 2 years allocated into 2 groups of 10 individuals each. Group I was dairy goat experiment not induced with the oxytocin hormone as the control. Group II was dairy goat experiment induced with the oxytocin hormone at a dose of 1 ml (10 IU) intramuscularly before milking. Milk production was measured morning and evening as daily milk production in milliliters (ml). Milk was given to the kid of each parent. The kid's performance was measured based on the daily weight gain of the kid during the study. Overall, the application of science and technology could be adopted by farmers, and oxytocin-induced dairy goat milk production (503.2 ml) was significantly higher (P<0.05) than control (305.4 ml) with an increase of 64.77%, with a positive level of correlation (r = 0.45) and contributed 19.83% to the kids daily body weight gain.